The use of pre-existing CT imaging in screening for abdominal aortic aneurysms. (December 2016) - Ruff, Allison; Patel, Krishna; Joyce, Jennifer R; Gornik, Heather L; Rothberg, Michael B
Ultrasound screening for abdominal aortic aneurysm (AAA) is recommended for male smokers >65 years of age, but screening rates remain low. If computed tomography (CT) performed for other indications could be considered adequate for screening, one-third of ultrasounds would potentially be unnecessary, and overall screening rates would be substantially higher. The objective of this study was to evaluate the sensitivity of CT imaging of the abdomen for the detection of AAA when performed for other clinical indications. We performed a retrospective study of patients eligible for AAA screening who had undergone an abdominal ultrasound as well as an abdominal CT scan for other indications within 3 years prior to that study. The primary outcome was identification of an AAA, recorded in the findings narrative or impression of the CT scan report. Of 142 patients with both a CT scan and an AAA on ultrasound, 127 (89.4%) were noted to have an AAA in the report of a CT scan performed within the 3 years prior to the ultrasound. An additional 10 films demonstrated an AAA that was not mentioned in the report. The sensitivity of pre-existing CT scans for AAA screening was 97.2% (137/141) [95% CI: 93.4–99.0%]; 123 (86.6%) of these positive findings were reported in the findings narrative and 120 (84.5%) were reported in the radiologist's final impression. The sensitivity for AAA identification in the report of a pre-existing CT scan of the abdomen performed for alternate indications appears high enough to use as a screening test. When radiologists note an AAA, they should be sure to include it in the final impression.